2017
DOI: 10.1136/bmjoq-2017-000095
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication between obstetric and neonatology teams for high-risk deliveries: a quality improvement project

Abstract: Summoning is a key component of communication between obstetrics and neonatal resuscitation team (NRT) in advance of deliveries. A paging system is a commonly used summoning tool. The timeliness and information contained in the page help NRT to optimally prepare for postdelivery infant care. Our aim was to increase the frequency that summoning pages contained gestational age and reason for NRT attendance to >90%. At baseline, 8% of pages contained gestational age and 33% of pages contained a reason for NRT att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recent research reports have suggested that missing information regarding one or more of the core content elements can potentially cause adverse outcomes for the newborn and/or the mother 17 18. To identify missing elements, after all handovers were coded using the clinical content framework, we evaluated each handover for content completeness and content relevance .…”
Section: Methodsmentioning
confidence: 99%
“…Recent research reports have suggested that missing information regarding one or more of the core content elements can potentially cause adverse outcomes for the newborn and/or the mother 17 18. To identify missing elements, after all handovers were coded using the clinical content framework, we evaluated each handover for content completeness and content relevance .…”
Section: Methodsmentioning
confidence: 99%
“…However, there can be significant practice variation between and even within centers regarding how the neonatal resuscitation team is activated. For example, prior to the implementation of a quality improvement effort aimed at improving this communication, one center identified that only 8% of pages to the neonatal resuscitation team contained the fetus’ gestational age and just 33% of pages contained the reason for requesting the neonatal resuscitation team [43]. The process that resulted from this quality improvement work included a number of systems-based strategies to improve communication between the obstetric team and the neonatal resuscitation team, including the training of staff, a decrease in the number of categories of information that were transmitted, and the implementation of a software-based program to aid standardized information gathering and dissemination [43].…”
Section: Macroergonomic Challengesmentioning
confidence: 99%